Praktik Utang Piutang Tanpa Surat pada Acara Walimatul’ursy di Desa Sembawa: Sebuah Tinjauan Hukum Islam - Mualim, Mualim; Muhlisoh, Elis; Agustine, Hendra Karunia (Al Barakat, 2024)
The practice of debts and receivables using an unwritten "ttip" system at the walimatul'ursy event has been widely carried out by the people of Sembawa Village, Jalaksana District, Kuningan Regency, where people who have more assets such as basic necessities or money will entrust their assets to family, neighbors or the community who will carry out the walimatul'usry. However, it is not yet known in detail how accounts payable and receivable practice with this unwritten 'entrustment' system. This research aims to examine the practice of debts and receivables using an unwritten 'entrustment' system at the walimatul'ursy event in Sembawa Village, Jalaksana District, Kuningan Regency and a review of Islamic law towards the practice of debts and receivables using an unwritten 'entrustment' system at the walimatul' event. ursy in Sembawa Village, Jalaksana District, Kuningan Regency. This research uses qualitative methods and is a type of field research. The data collection technique used is a semi-structured interview technique and uses two data sources, namely primary data sources and secondary data sources. The results of this research show that first, the practice of debts and receivables using an unwritten 'entrustment' system is a tradition called kondangan and nitip. This practice is carried out by providing assistance in the form of money or basic necessities when neighbors, relatives or the community are holding a celebration such as a wedding (walimatul'ursy), circumcision (walimatul'khitan), building a house, someone dies, someone is sick and so on. This practice is a very easy process, there are no conditions whatsoever and there are two types of goods debt returns, namely those that are similar and those that are not. Second, based on a review of Islamic law, the practice of debts and receivables using an unwritten 'entrustment' system in Sembawa Village is in accordance with Islamic law, because it fulfills the pillars and requirements of qordh. However, in practice, some returns are in accordance with the provisions of Islamic law, some are not. Apart from that, the practice of debts and receivables using an unwritten "entrustment" system at the walimatul'ursy event in Sembawa Village is a good habit aimed at helping each other (ta'awun) which has been carried out from generation to generation from the time of our ancestors until now. and is well accepted by society and this practice is included in urf, because it fulfills all the requirements of authentic urf.